Arhgap21 Deficiency Results in Increase of Osteoblastic Lineage Cells in the Murine Bone Marrow Microenvironment - Pissarra, Mariana Ferreira; Torello, Cristiane Okuda; Gomes, Rafael Gonçalves Barbosa; Shiraishi, Rodrigo Naoto; Santos, Irene; Vieira Ferro, Karla Priscila; Lopes, Matheus Rodrigues; Bergamo Favaro, Patricia Maria; Olalla Saad, Sara Teresinha; Lazarini, Mariana (Frontiers in Cell and Developmental Biology, 2021)
ARHGAP21 is a member of the RhoGAP family of proteins that is involved in cell growth, differentiation, and adhesion. We have previously shown that the heterozygous Arhgap21 knockout mouse model (Arhgap21+/-) presents several alterations in the hematopoietic compartment, including increased frequency of hematopoietic stem and progenitor cells (HSPC) with impaired adhesion in vitro, increased mobilization to peripheral blood, and decreased engraftment after bone marrow transplantation. Although these HSPC functions strongly depend on their interactions with the components of the bone marrow (BM) niche, the role of ARHGAP21 in the marrow microenvironment has not yet been explored. In this study, we investigated the composition and function of the BM microenvironment in Arhgap21+/- mice. The BM of Arhgap21+/- mice presented a significant increase in the frequency of phenotypic osteoblastic lineage cells, with no differences in the frequencies of multipotent stromal cells or endothelial cells when compared to the BM of wild type mice. Arhgap21+/- BM cells had increased capacity of generating osteogenic colony-forming units (CFU-OB) in vitro and higher levels of osteocalcin were detected in the Arhgap21+/- BM supernatant. Increased expression of Col1a1, Ocn and decreased expression of Trap1 were observed after osteogenic differentiation of Arhgap21+/- BM cells. In addition, Arhgap21+/- mice recipients of normal BM cells showed decreased leucocyte numbers during transplantation recovery. We also found an upregulation of ARHGAP21 in BM mesenchymal stromal cells of patients with acute myeloid leukemia (AML). Our data suggest participation of ARHGAP21 in the remodeling of the BM microenvironment through the disruption of the osteoblastic niche. In AML, increased ARHGAP21 expression may be associated with recent findings of impaired osteolineage maturation and reduction of osteocalcin serum levels.